Cooperative operation based master-slave in islanded microgrid with CPT current decomposition - Mortezaei, Ali; Simões, M. Godoy; Marafão, Fernando P. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2015)
In multi-inverter-based islanded microgrids with unbalanced and distorted loads, due to voltage drop across line, the load bus voltage is unbalanced and distorted, which shows the requirement for power quality increase at load bus. To address this problem, this paper presents master-slave-based cooperative operation of DGs with the implementation of Conservative Power Theory (CPT), in which in addition to load sharing, load voltage quality is also improved to standard limits. Sharing factors for each current component are determined by a supervisory control considering constraints for instance availability of primary sources, converter rating and structure and switching frequency. The control strategy is implemented in abc frame. This remarkably facilitates the controller design procedure, offering a very flexible, selective and powerful load current sharing scheme for the DG inverter units, and the effectiveness of this scheme is demonstrated through digital simulations conducted by means of PSIM.
Keywords: Conservative Power Theory; Cooperative Control; Current Sharing; Distributed Generation (DG); Microgrid; Power Quality Improvement